Law and State Practice in Armenia - Sarkin, Jeremy (2022)
This article deals with missing persons in Armenia. So far around 5,000 people from all sides in the Nagorno-Karabakh conflict have been reported as having gone missing. This article contextualises the democratic and human rights situation in Armenia and argues that if progress is to occur, there needs to be a coordinating mechanism involving all conflict parties to search, recover, and identify the missing. One sign of progress is that a new Commission – the Inter-Agency Commission on POWs, Hostages and Missing Persons – was established in Armenia in 2019, and a new decree adopted. However, it needs to be reformed to allow it to be better suited to achieve the necessary goals. The study examines the law on the missing and finds that there is much confusion about the legislation, as it is scattered and often vague and unclear. The laws are aimed at, and applicable to, criminal cases, and not the humanitarian nature of such instances. It therefore argues that a new law ought to be adopted. A variety of recommendations are made in the article such as the need to enhance information collection, to find potential burial sites, and to systematically map and protect possible burial sites to ensure that future recovery and identification processes are not hindered.